Causal associations of sleep traits with cancer incidence and mortality - Tian, Shanshan; Huangfu, Longtao; Bao, Yanping; Ai, Sizhi; Chang, Suhua; Wang, Qianwen; Zhu, Ximei; Yan, Wei; Shi, Jie; Shi, Le; Deng, Jiahui; Lu, Lin (Frontiers in Genetics, 2023)
To explore the correlation and causality between multidimensional sleep traits and pan-cancer incidence and mortality among patients with cancer. The multivariable Cox regression, linear and nonlinear Mendelian randomization (MR), and survival curve analyses were conducted to assess the impacts of chronotype, sleep duration, and insomnia symptoms on pan-cancer risk (N= 326,417 from UK Biobank) and mortality (N=23,956 from UK Biobank). In the Cox regression, we observed a linear and J-shaped association of sleep duration with pan-cancer incidence and mortality among cancer patients respectively. In addition, there was a positive association of insomnia with pan-cancer incidence (HR, 1.03, 95% CI: 1.00-1.06, P = 0.035), all-cause mortality (HR, 1.17, 95% CI: 1.06-1.30, P = 0.002) and cancer mortality among cancer patients (HR, 1.25, 95% CI: 1.11-1.41, P < 0.001). In the linear MR, there was supporting evidence of positive associations between long sleep duration and pan-cancer incidence (OR, 1.41, 95% CI: 1.08-1.84, P = 0.012), and there was a positive association between long sleep duration and all-cause mortality in cancer patients (OR, 5.56, 95% CI: 3.15-9.82, P = 3.42E-09). Meanwhile, a strong association between insomnia and all-cause mortality in cancer patients (OR, 1.41, 95% CI: 1.27-1.56, P = 4.96E-11) was observed in the linear MR. These results suggest that long sleep duration and insomnia play important roles in pan-cancer risk and mortality among cancer patients. In addition to short sleep duration and insomnia, our findings highlight the effect of long sleep duration in cancer prevention and prognosis.